2018
DOI: 10.1111/adj.12607
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in severe odontogenic infections of the South Australian population: a 9‐year retrospective audit

Abstract: There were moderate rates of antibiotic-resistant odontogenic infections within the South Australian population. Patients within this subgroup demonstrate markedly poorer clinical outcomes. Effective treatment of odontogenic infections involves early operative intervention, with adjunctive use of appropriate antibiotic therapy that involves close monitoring of response to removal of the cause and use of first-line antibiotic agents. Cases that fail to respond require urgent specialist review in order to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 17 publications
0
50
2
3
Order By: Relevance
“…Dental and medical practitioners must be aware that the primary treatment of odontogenic infection is prompt removal of the infective process, such as via dental extraction or endodontic debridement. The average cost of a single dental extraction in Australia at the conclusion of the study period was $181 Australian Dollars . This is a stark contrast to the financial sequelae of inpatient hospital admission reported in this study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Dental and medical practitioners must be aware that the primary treatment of odontogenic infection is prompt removal of the infective process, such as via dental extraction or endodontic debridement. The average cost of a single dental extraction in Australia at the conclusion of the study period was $181 Australian Dollars . This is a stark contrast to the financial sequelae of inpatient hospital admission reported in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…The average cost of a single dental extraction in Australia at the conclusion of the study period was $181 Australian Dollars. 10 This is a stark contrast to the financial sequelae of inpatient hospital admission reported in this study. Antibiotic treatment is an adjunctive treatment and should not replace expedient dental care for the patient presenting with acute dental infection.…”
Section: Discussioncontrasting
confidence: 63%
“…Antibiotic resistance and stewardship have been given inadequate attention in the dental industry until recently . A retrospective audit of antibiotic resistance in severe odontogenic infections in the South Australian population showed that the rate of overall antibiotic resistance was 17.8%, with the most resistance to penicillin and amoxicillin . These patients consequently had longer hospital stays and a higher incidence of non‐response to initial surgical therapy .…”
Section: Introductionmentioning
confidence: 99%
“…5 A retrospective audit of antibiotic resistance in severe odontogenic infections in the South Australian population showed that the rate of overall antibiotic resistance was 17.8%, with the most resistance to penicillin and amoxicillin. 16 These patients consequently had longer hospital stays and a higher incidence of non-response to initial surgical therapy. 16 Other studies have parallel findings and have shown that bacteria which are common isolates from odontogenic infections have proven to have a frequency of penicillin resistance around 5%-20%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation